Male Participation Factors in Antenatal Care for Maternal Health in Rural Areas: Systematic Review - Yolanda Safitri; Frima Elda (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Maternal health remains a critical global health priority, especially in rural areas where Antenatal Care (ANC) services often face significant challenges, including limited resources, low awareness, and cultural barriers. Male involvement plays a vital role in improving maternal health outcomes. This systematic review examines factors influencing male participation in ANC services in rural settings. A literature search was conducted using PubMed, ProQuest, and Scopus databases from 2019 to 2024. Keywords included "pregnant woman," "rural population," "antenatal care," "patriarchal culture," and "men involvement". After filtering, 17 relevant articles were selected based on CEBM study quality. The study included qualitative, quantitative, and mixed-method research on male participation in ANC at both community and facility levels. Only studies published in English within the specified timeframe were included, while duplicates, non-English articles, and studies outside the rural context were excluded. Among the selected studies, eight were quantitative, six qualitative, and three employed mixed methods. Findings reveal that education, social norms, economic factors, and policies significantly influence husbands' involvement in ANC, aligning with previous research. However, this review highlights key differences, particularly in the impact of social changes that promote greater male participation and the role of concrete policies in enhancing their access to ANC. To improve husband involvement, targeted interventions are necessary, including couple-based educational programs, enhanced accessibility and affordability of health services, and shifts in community attitudes toward men's roles during pregnancy. Addressing these factors is essential for improving maternal health outcomes in rural settings.